Biohydrogen production via integrated sequential fermentation using magnetite nanoparticles treated crude enzyme to hydrolyze sugarcane bagasse - Srivastava N.; Alhazmi A.; Mohammad A.; Haque S.; Srivastava M.; Pal D.B.; Singh R.; Mishra P.K.; Vo D.V.N.; Yoon T.; Gupta V.K. (My University, 2025)
This study presents a potential approach to enhance integrated sequential biohydrogen production from waste biomass using magnetite nanoparticle (Fe3O4 NPs) which is synthesized through waste seeds of Syzygium cumini. Consequences of 0.5% Fe3O4 NPs have been investigated on the thermal and pH stability of fungal crude cellulase. It is noticed that Fe3O4 NPs treated enzyme and control exhibits 100% activity in the temperature range of 45–60 °C and 45–55 °C, respectively. Moreover, Fe3O4 NPs treated enzyme showed extended thermal stability in the temperature range of 50–60 °C up to 12 h. Beside this, Fe3O4 NPs treated enzyme possesses 100% stability in the pH range of 5.0–7.0 whereas control exhibited only at pH 6.0. Enzymatic hydrolysis via Fe3O4 NPs treated enzyme has been employed which produces ∼68.0 g/L reducing sugars from sugarcane bagasse. Subsequently, sugar hydrolyzate has been utilized as substrate in the sequential integrated fermentation that produces ∼3427.0 mL/L cumulative hydrogen after 408 h. This approach may have potential for the pilot scale production of biohydrogen from waste biomass at low-cost in an eco-friendly manner. © 2021